2020
DOI: 10.3389/fmicb.2020.593215
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Mechanisms to Antimicrobial Peptides in Gram-Positive Bacteria

Abstract: With the alarming increase of infections caused by pathogenic multidrug-resistant bacteria over the last decades, antimicrobial peptides (AMPs) have been investigated as a potential treatment for those infections, directly through their lytic effect or indirectly, due to their ability to modulate the immune system. There are still concerns regarding the use of such molecules in the treatment of infections, such as cell toxicity and host factors that lead to peptide inhibition. To overcome these limitations, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 271 publications
(334 reference statements)
0
68
0
Order By: Relevance
“…The effect of this AMP might be more efficient at these high concentrations against members of Gram-positive species, a hypothesis that needs to be verified in further studies. The differences between the cell walls of Gram-positive and -negative bacteria according the murein layer and the composition might be an explanation for the higher MIC values of the two S. aureus strains compared the tested E. coli [ 75 ]. Furthermore, Gram-positive bacteria are able to partially neutralize their cell wall to resist AMPs [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of this AMP might be more efficient at these high concentrations against members of Gram-positive species, a hypothesis that needs to be verified in further studies. The differences between the cell walls of Gram-positive and -negative bacteria according the murein layer and the composition might be an explanation for the higher MIC values of the two S. aureus strains compared the tested E. coli [ 75 ]. Furthermore, Gram-positive bacteria are able to partially neutralize their cell wall to resist AMPs [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genus Staphylococcus causes different infections in the human population like impetigo, scalded skin syndrome, toxic shock syndrome, pneumonia, endocarditis, and urinary tract infections, among others [ 23 ]. Some species of this genus are resistant to antibiotics, such as methicillin-resistant Staphylococcus aureus (MRSA) [ 24 ].…”
Section: Antibacterial Activity Of Propolismentioning
confidence: 99%
“…Regardless of the ways of and reasons for infection development, a frequent issue is antibiotic treatment. Indeed, staphylococci are not outsiders to the antimicrobial resistance and multidrug resistance (MDR) problem [ 17 ]. Different authors have reported a decreased susceptibility to β-lactams, clindamycin, tetracyclines, and (less frequently) fluoroquinolones and trimethoprim-sulfamethoxazole [ 10 , 11 , 12 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%